Masticatory movements and food textures in older patients with eating difficulties. (21st October 2021) - Kato, Yoko; Kikutani, Takeshi; Tohara, Takashi; Takahashi, Noriaki; Tamura, Fumiyo
Abstract: Objectives: To investigate whether masticatory movements in older patients with eating difficulties were associated with oral motor function, physical function, and appropriate food textures. Background: There are few reports on the association between masticatory movements and food textures in older patients with eating difficulties. Materials and Methods: This cross‐sectional study involved outpatients at a clinic that specialised in eating and swallowing rehabilitation. Masticatory movements were evaluated as normal or abnormal masticatory path patterns. Oral and physical functions were assessed in terms of oral and physical status, muscle strength and motor skills. The appropriate food texture was determined based on fibreoptic endoscopic evaluation of swallowing and a video fluoroscopic swallowing study. The associations between food texture and masticatory organ, muscle strength and motor skills were analysed. Results: A total of 126 outpatients (75 men and 51 women; mean age, 78.2 years; SD, 9.6 years) were included in the analysis. 68 participants (54.0%) showed abnormal masticatory movements. Masticatory movement was associated with masticatory performance (odds ratio [OR] = 0.99, 95% confidence interval [CI] = 0.98‐0.99), oral diadochokinesis (OR = 0.55, CI = 0.35‐0.86) and stepping test (OR = 0.92, CI = 0.86‐0.97). Masticatory movement (OR = 2.94, CI = 1.23‐7.01) and the number of natural teeth (OR = 0.94, CI = 0.89‐0.99) were associated with normal food. Conclusion: Masticatory movements in older patients with eating difficulties may be associated with appropriate food textures whilst being influenced by individual differences in systemic motor control. Masticatory movements may be as important as teeth to enjoy eating.